PENINGKATAN KEMAMPUAN OPERASI PERKALIAN DENGAN MEDIA BENDA-BENDA TERDEKAT PADA PELAJARAN MATEMATIKA - Herdiaswati, Lurit (Jurnal Likhitaprajna, 2018)
The low mastery of the ability to multiplication in learning is due to the lack of proper learning models and the media used. This study uses the Classroom Action Research (CAR) approach. In the first cycle of action the mastery of the material before learning was given 31%, after the activity took place activists showed students: 58% active students, 30% moderate students, and 12% passive students. Student cooperation: 62% active students, 28% moderate students, and 10% passive students. While the average evaluation results were 68 with students completing 33 students and 16 students had not finished. The results of action in the second cycle of material mastery before the action was 48%. After the action is carried out student activities: active students78%, students are 18% and passive students 4%. Student cooperation: 84% active students, 14% moderate students, and 2% passive students. Evaluation results averaged 76 with students completing 46 students completed and 3 students not yet completed.Keywords: multiplication, media of learning, mathematics